Potensi antitumor dari beberapa spons laut asal teluk Manado - Wilson Alexander Raymond Rombang (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Screening of antitumor for the extract and fraction from the marine sponges ofManado Gulf, Aaptos sp., Acervochalina sp., Gelliodes sp., Theonella sp., and orangeboring sponge have been done by use P388 murine leukemia cell. Activity test resultshowed IC50 of the extract and fraction from Aaptos sp were: MeOH extract 5938ng/mL and BuOH extract 125000 ng/mL; Acervochalina sp: EtOH extract 125000ng/mL, PE extract 125000 ng/mL, EtOAc extract 4251 ng/mL, BuOH extract125000 ng/mL; Gelliodes sp: EtOH extract 125000 ng/mL; Theonella sp: EtOHextract 125000 ng/mL, PE extract 9282 ng/mL, EtOAc extract 3273 ng/mL, BuOHextract 125000 ng/mL; orange boring sponge: MeOH extract 1422 ng/mL. Based onthe IC50 value, it could be concluded that MeOH extract of Aaptos sp., EtOAc extractof boring sponge could be a sources for cytotoxic compounds.